Mathematics Using Discovery Learning Model: Improve Creative Thinking on Exponent Function Material - Muhammad Farid Nasrulloh; Annisa Dyah Hestiana; Fitri Umardiyah; Faisol Hidayatulloh (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
Learning difficulties can be interpreted as the inability of students to complete tasks from the teacher. In mathematics learning, difficulties in understanding the material have become commonplace, this is because mathematics is considered difficult by students. This study was conducted with the aim of determining the process and influence of creative thinking skills of class X students of SMK Kreatif Bahrul Ulum before and after implementing the discovery learning model. The research method used is pre-experimental design with a one-group post-test design type and using a quantitative approach. The research instruments used were tests and non-tests. The data analysis technique used was a hypothesis test. However, before conducting a hypothesis test, the data obtained was first tested for normality and homogeneity. Based on the calculation of the paired sample t-test, it showed that the t-count value was 19.453 with a significance of 0.000. The significance value showed 0.000 <error level of 0.05, so it can be concluded that Ha is accepted. The acceptance of Ha indicates that there is an increase in the creative thinking skills of class X students of SMK Kreatif Bahrul Ulum Tambakberas before and after implementing the discovery learning model.